The impact of land development on the distribution of road noise level on the surface of the upper wildlife crossings - Sołowczuk, Alicja (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The Environmental Protection concerns mainly the fauna, because the development of communication and the construction of new transport routes has been increasingly fragmenting the natural environment. To fix the errors, arising from the fragmentation of the natural environment, upper or lower crossings are built for animals. The upper crossings are very expensive because of their dimensions. The construction of the upper crossings does not always turn out to be functional, as badly developed surfaces are not attractive to animals, which do not use them. The proper management of the upper crossings area is a very difficult issue, still quite experimental. In the literature, no functional solutions can be found in this regard. The only guidelines for designers may be the examples of the area development of the existing crossings, whose functionality was confirmed by the data from monitoring. However, ready solutions from other roads and natural conditions are not always useful, because in most cases the crossings should be tailored to the wildlife which use them. The paper presents various development elements, together with the results of noise analyzes, confirming the impact of the development, depending on its type, on the ”achieved status of soundproofness” on the access to the crossings and their surface.